Independent psychometric validation of European Organization for Research and Treatment of Cancer Quality of Life Questionnaire‐Endometrial Cancer Module (EORTC QLQ‐EN24). (6th January 2017) - Stukan, M.; Zalewski, K.; Mardas, M.; Filarska, D.; Szajewski, M.; Kmieć, A.; Bińkowska, P.; Pietrzak‐Stukan, M.; Dudziak, M.; Grabowski, J.P.; Eskander, R.N.; Greimel, E.
Abstract : The endometrial cancer (EC)‐specific Quality of Life module of the European Organization for Research and Treatment of Cancer (EORTC QLQ‐EN24), was developed and validated in one study. We independently validated and assessed the psychometric properties of the instrument. Two hundred and eight women with EC before surgery, during adjuvant treatment and follow‐up; in three different cancer centres completed the EORTC QLQ‐C30 and the EN24. The questionnaire's completion rate was 100%, except sexuality items, that were answered by 35% of patients. All item‐scale correlations for the multi‐item scales exceeded the .4 criterion and correlated well with their own scale, while correlations with the other scales were low. The internal consistency of all multi‐item scales were satisfactory (Cronbach's alpha coefficients ranging from .77 to .97). Discriminance for single‐item scales was low. The QLQ‐EN24 module discriminated well between clinically different patients, and there were no differences in quality of life questionnaire scales between patients with body mass index ≤30 when compared to those with >30. This validation study supports the reliability, as well as convergent and divergent validity of the EORTC QLQ‐EN24. The module is a useful instrument for the assessment of QOL in patients with EC. However, data concerning sexuality should be interpreted with caution.